Colorectal Cancer in Africa: Causes, Dietary Intervention, and Lifestyle Change - Oluwatoyin, B. Oluwole; Viola, A. Nwachukwu Nicholas-Okpara; Elemo, Gloria; Deborah, Ibekwe; Ijeoma, Eboagwu; Olubunmi, Elemo; Adeyoju, Olubamike Adetutu; Nnenna, Efuribe; Maryam, Olanshile Adegboyega (International Journal of Nutrition, 2021)
Colorectal cancer (CRC) is a menace in the global public health system. According to GLOBOCAN reports, colorectal cancer is the second most diagnosed cancer in the world with more than 1.9 million cases and 935,000 deaths in 2020 alone. Diet plays a key role in exposing humans to environmental carcinogens and anti-carcinogens, consequently mitigating or aiding in the development of various cancers. CRC is most prevalent in western countries with a high intake of saturated fats, refined carbohydrates, and processed meat. CRC was an extremely rare disease in Africa some decades ago, but the situation is fast changing. The traditional African diet consists of leafy, roots and cruciferous vegetables, fruits, roots, tubers and plantains, legumes, whole grains, and spices, all of which have been shown to possess protective effects against CRC. However, the effect of urbanization has contributed to the shift of dietary choices among the African population to consuming more ultra-processed foods with high levels of unhealthy components that have originated from colorectal cancer prevalent regions. This review evaluates the current nutritional challenges of the African diet to colorectal cancer and the potential roles of the traditional African diets and lifestyle modification in the prevention and management of colorectal cancer.
Keywords: Colorectal cancer; Traditional African diets; Africa